A Novel Electrochemical Differentiation between Exosomal-RNA of Breast Cancer MCF7 and MCF7/ADR-Resistant Cells - Mohammed H. Abdelaziz; Ehab N. El Sawy; Anwar Abdelnaser (MDPI AG, 2023)
Cancer is considered one of the most burdensome diseases affecting lives and, hence, the economy. Breast cancer is one of the most common types of cancer. Patients with breast cancer are divided into two groups: one group responds to the chemotherapy, and the other group resists the chemotherapy. Unfortunately, the group which resists the chemotherapy is still suffering the pain associated with the severe side effects of the chemotherapy. Therefore, there is a critical need for a method to differentiate between both groups before the administration of the chemotherapy. Exosomes, the recently discovered nano-vesicles, are often used as cancer diagnostic biomarkers as their unique composition allows them to represent their parental cells, which makes them promising indicators for tumor prognosis. Exosomes contain proteins, lipids, and RNA that exist in most body fluids and are expelled by multiple cell types, including cancer cells. Furthermore, exosomal RNA has been significantly used as a promising biomarker for tumor prognosis. Herein, we have developed an electrochemical system that could successfully differentiate between MCF7 and MCF7/ADR depending on the exosomal RNA. The high sensitivity of the proposed electrochemical assay opens the door for further investigation that will address the other type of cancer cells.